Perancangan Database Berbasis Wersip di Kantor Pusat Komputer Universitas Negeri Padang - Febrina, Ayu; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discusses about the design of a web-based database as the retrieval media of archive in main computer office of UNP. This writing aims to describe how to design a web-based database as the retrieval media of archive in main computer office of UNP, so it can help the process of finding the archives that required quickly and accurately. There are some steps in design a web-based the retrieval media of archive. First, the retrieval media of archive can be more effective tool in supporting the management of archive in main computer office of UNP. Second, the retrieval media of archive can be used as an alternative tool of archival storage from paper into non-paper that can be stored into a computer database. Third, the retrieval media of archive can be as a searching tool of archive that has stored into the database quickly and accurately. Fourth, the retrieval media of archive provides a lot of convenience for archivists in terms of the search and management. Keywords: database; retrieval; search